2009
DOI: 10.3855/jidc.471
|View full text |Cite
|
Sign up to set email alerts
|

Deletion, insertion and stop codon mutations in vif genes of HIV-1 infecting slow progressor patients

Abstract: Background: Variable progression towards AIDS has been described and has been related to viral and host factors. Around 10% of the HIV-1 infected patients are slow progressors (SP), not presenting with AIDS disease signs even after more than 10 years of infection. Viral gene defects have been associated with the disease progression but more studies are still needed. Methodology: The sequence of vif and nef were analyzed for HIV-1 infecting 14 SP and 46 normal progressors (NP) patients. Results: Co-circulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…No primary resistance mutation was detected and no differences were observed in the frequency of secondary mutation associated with drug resistance between pol sequences obtained from HIV-1-positive patients co-infected or not with GBV-C. In vif, the amino acid substitution R132K has been associated with lower viral load in patients harboring viruses with this polymorphism compared to patients carrying viruses with wild type vif [12,18]. Although this substitution was observed in 18/47 (38.3%) of the sequenced viruses, no statistically significant difference was observed in the frequency of this polymorphism between HIV-1 + GBV-C + and HIV-1 + GBV-C -( Table 2).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…No primary resistance mutation was detected and no differences were observed in the frequency of secondary mutation associated with drug resistance between pol sequences obtained from HIV-1-positive patients co-infected or not with GBV-C. In vif, the amino acid substitution R132K has been associated with lower viral load in patients harboring viruses with this polymorphism compared to patients carrying viruses with wild type vif [12,18]. Although this substitution was observed in 18/47 (38.3%) of the sequenced viruses, no statistically significant difference was observed in the frequency of this polymorphism between HIV-1 + GBV-C + and HIV-1 + GBV-C -( Table 2).…”
Section: Resultsmentioning
confidence: 93%
“…Partial or complete coding regions of HIV-1 pol, vif, env, and nef genes were amplified and sequenced as previously described [12,16]. For the pol gene, only antiretroviral-naïve patients were selected for sequence analysis.…”
Section: Hiv-1 Molecular Characterizationmentioning
confidence: 99%
“…Regarding gross deletions, to date, only two patients have demonstrated gross deletions in the vif gene [17, 18] and only one patient has demonstrated the insertion of two amino acids, and these patients were part of a nonprogressing mother-child pair [28]. However, in our present study, of the 10 LTSP patients who were assessed, four patients demonstrated gross deletion in the vif gene during KRG intake prior to receiving HAART (1.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations at positions 72 and 77 in Vpr, disrupting the viral protein function, were frequently detected in non-progressors [58, 59]. Finally, single or large insertions in Vpu [60] and amino acid substitutions in Vif [61, 62] have also been associated with non-progression in HIV-1 disease.…”
Section: Introductionmentioning
confidence: 99%